Ethical-philosophical aspects of death: between moral responsibility and dehumanization - Correa Cetina, Edwin Augusto (Universidad Pedagógica y Tecnológica de Colombia, 2019)
In past times, the transgression of the norm that prohibits to murder another human being was supported in supernatural believes. In hostile times, the norm was removed to provide a room for the congenital sadism of human beings; however, there have been several scenarios and causes where death becomes protagonist. Following this direction, this work, in its first part, explores the freaky sense designated to death in archaic eras. Besides, a dialogue and a confrontation appear and spring from the possibility-impossibility and continuity-discontinuity concepts. In the second part, a contextualization of war and extermination as dynamical protagonists of cruelty. Dehumanization and the archaic inheritance of violence are highlighted as axis that gravitate around the body destruction of unnumbered subjectivities. In the third part, individual responsibility is analyzed before the abominable great Other. As a manner of end, we expose how to die by Other’s desire is legitimized by the state.